Growth, biomass production and nutrient accumulation of Macaranga gigantea in response to NPK fertilizer application - DWI SUSANTO; SRI MULYATI; HERI PURNOMO; DADDY RUHIYAT; RUDIANTO AMIRTA (Nusantara Bioscience, 2017)
Susanto D, Mulyati S, Purnomo H, Ruhiyat D, Amirta R. 2017. Growth, biomass production and nutrient accumulation of Macaranga gigantea in response to NPK fertilizer application. Nusantara Bioscience 9: 330-337. Research described in this paper investigated the effect of fertilizer application on the growth, biomass production and nutrient accumulation of mahang (Macaranga gigantea) plant components. The experiment was carried out in a research area of the Faculty of Forestry, Mulawarman University, Samarinda, East Kalimantan. The effects of five dose levels of an NPK (16-16-16) fertilizer on the growth rate of mahang seedlings planted in field conditions were compared. The treatments consisted of a control group (with no fertilizer), and dosages of 40 g, 80 g, 120 g and 160 g per plant. Fertilization at those levels was applied twice: the first application at four weeks after the planting and the second application at 6 months after the first. Growth rates between treatments were compared over a twelve month period. The research findings revealed that as the dosages of fertilizer increased, so the growth, biomass production and nutrient accumulation in components of the plants also increased. The best growth was found in the treatment in which fertilizer was applied (twice) at a dosage of 120 g per plant; at this dose level, by twelve months of age, the stem basal diameter had reached 45.2ï‚±4.9 cm, stem height 219.2ï‚±39.1 cm, number of leaves per plant 17.3ï‚±1.2, and canopy diameter 246.7ï‚±25.0 cm. The highest production of above-ground biomass was also found in the fertilizer treatment of 120 g per plant; the largest proportion of the biomass was in the leaves, followed by the wood, and then bark. The nutrient element that had accumulated most in plants at 1 year of age was potassium, followed by phosphorus and then nitrogen. The highest nitrogen uptake of stands was found in the NPK fertilization with a dosage of 160 g per tree, while the highest phosphorus and potassium uptake was found at a fertilizer dosage of 120 g per tree. The amount of nutrients accumulated in producing one tonne of above-ground biomass increased in response to different fertilization treatments. The fertilizer treatment of 120 g per plant (applied twice; the first soon after planting and the next after 6 months) resulted in the accumulation within the 1 year old plants of 2.38 kg of nitrogen, 6.36 kg of phosporus and 17.83 kg of potassium, with an N:P:K ratio of 13.3 : 35.6 : 100. The availability of the element potassium needs special attention when this species is cultivated.